Development of a Health Literacy Model Based on the One Student One Family Support Method for Pulmonary Tuberculosis Prevention in Rural Communities - Ulfa Maulidah; Elena V. Markovic (Athallah Publishing, 2026)
Place the question addressed in a broad context. Write the research objectives concisely and clearly Families need to pay attention by involving nursing students to enhance the role of family members in assisting the family's knowledge about pulmonary tuberculosis and how to care for sick family members, as well as its prevention. The aim of this study is to identify the knowledge, attitudes, and behaviors of families in the prevention of pulmonary tuberculosis in the Boroko Community Health Center area of North Bolmong Regency in the intervention and control groups. Methods: the research method used in this study is a quasi-experiment pre-post-test with a control group design. This research will conduct health literacy model assistance involving nursing students as companions and providing support to families with members suffering from tuberculosis for 8 weeks with a total of 14 meetings. The sampling technique uses stratified random sampling according to the established criteria, and the sample selection uses Slovin's formula, resulting in 52 respondents consisting of 26 for the intervention group and 26 for the control group. The research results indicate that there is a significant difference between the knowledge, attitudes, and behaviors of the intervention group and the knowledge of the control group. The assistance of nursing students as support providers in the family has an impact on the knowledge, attitudes, and behaviors of patients in preventing tuberculosis.